The use of ICS/LABA (extra-fine and non-extra-fine) in elderly asthmatics - Benfante A (Therapeutics and Clinical Risk Management, 2016)
Alida Benfante, Marco Basile, Salvatore Battaglia, Mario Spatafora, Nicola Scichilone Biomedical Department of Internal and Specialist Medicine, University of Palermo, Palermo, Italy Abstract: Age represents an exclusion criterion in randomized clinical trials designed to test the efficacy and safety of inhaled drugs in asthma. As a consequence, data on efficacy and safety of inhaled corticosteroid (ICS) and long-acting ß2 agonist (LABA) combinations in elderly asthmatics are scanty. Older age is associated with an increased proportion of comorbid conditions; in addition, all organ functions undergo a process of senescence, thus reducing their ability to metabolize the agents. Overall, these age-associated conditions may variably, and often unpredictably, affect the metabolism and excretion of respiratory drugs. However, pharmacological treatment of asthma does not follow specific recommendations in the elderly. In the elderly, the ICS/LABA combinations may carry an increased risk of local indesiderable effects, primarily due to the lack of coordination between activation of the device and inhalation, and systemic adverse events, mainly due to the greater amount of active drug that is available because of the age-associated changes in organ functions as well as drug-to-drug and drug-to-concomitant disease interactions. The extra-fine formulations of ICSs/LABAs, which allow for a more favorable drug deposition in the lungs at a reduced dose, may contribute to overcome this issue. This review revises the efficacy and safety of treatment with ICSs/LABAs, focusing on the main pharmacodynamic and pharmacokinetic properties of the drugs and highlighting the potential risks in the elderly asthmatic population. Keywords: aging, comorbidity, lung function, inhaled corticosteroids, long-acting ß2 agonists, asthma treatment